Pollen-mediated flow of bar gene in transgenic herbicide-resistant turf grass Zoysia japonica - Kang, Hong-Gyu; Chung, Ok-Chul; Bae, Tae-Woong; Sun, Hyeon-Jin; Song, In-Ja; Park, Kee Woong; Lim, Pyung-Ok; Lee, Jaechun; Lee, Yong-Eok; Song, Pill-Soon; Lee, Hyo-Yeon (Plant biotechnology reports, 2021)
Weed control can be most effectively achieved through the use of herbicide-resistance transgene. A preliminary study bar -transgenic Zoysia japonica posed no serious risk on the unintended escape of the transgene from its cultivation site. The present follow-up investigation of the dispersion of pollen and its short-distance escape outside of the bar -transgenic Zoysia japonica habitats were ascertained in terms of environmental factors affecting anthesis and pollen viability. In a 24-h day cycle, zoysiagrass pollen was released predominantly between 08:00 and 10:00, and the pollen was most viable during the same time interval. Optimal temperature and humidity for pollen viability was 15–20 °C and 80–90%, respectively. The pollen germinated in 120 min after anthesis, but under cloudy conditions germination time doubled. No differences in pollen viability/longevity between the transgenic and non-transgenic plants were observed. The pollen-mediated gene flow of transgenic Zoysia japonica to wild-type non-transgenic zoysiagrass species was monitored by measuring the cross-over rate of the bar gene in the context of three different models. At distances within 5 m, the rate of gene flow ranged from 3 to 5.7% according to the models used. The greater the distance from the transgenic plant site, the lower the gene flow rate. The furthest transgene detected was 38 m away and exhibited a 0.25% gene flow rate. The radial model yielded a 3.7% escape rate within a 3 m radius and was wind direction dependent. The distance- and direction-dependent gene flow events were influenced by wind direction and velocity during flowering season.